Pengaruh keterlibatan dalam muzik terhadap kesejahteraan hidup dan dorongan memilih kursus muzik dalam kalangan pelajar Universiti - Shamsul Amri, Abdul Manap (2019)
Music is seen as one of the elements and factors that color and compliment our everyday lives. However, the engagement in music can affect the well-being of an individuals and can encourage certain university students to choose music related courses. This study was conducted to examine the extent to which the legitimacy of involvement in the music can affects the wellbeing of an individuals and can encourage a university students to choose a music related courses. Based on the Uses and Gratifications Theory, the three instruments that have been developed have been used to examine this study: Music USE, personal wellbeing index for adult and motivation measures. A survey using the Google form has been distributed online. A total of 329 respondents consisting of students involved with formal and informal learning about music, which is the music management major, music co-curriculum students and active performing students of UUM's Center for Culture and Art. The data obtained were analyzed descriptively in mean and standard deviation of SPSS. While the inference analysis was implemented using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SMARTPLS 3.0. The results show that music involvement in the past influenced the well-being of the individual and encouraged them to choose music related courses. Based on the concept of the framework used in this study, modifications to engagement activities, human emotions and even courses, allow a new study to be made. The findings can also be used as inputs to the youth well-being index in Malaysia as well as a guide of students’ enrollment in music-related courses at Malaysia’s institutions of higher learning.